Design and Development of 2D Animation Media on Saving Money to Promote Saving Behavior among Children and Youth - หาญละคร ชัญญานุช; กาโน จักรพงษ์; ดีเจริญชิตพงศ์ จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to (1) Design and Development of 2D Animation Media on Saving Money to Promote Saving Behavior among Children and Youth, (2) Promote awareness and understanding of the importance of saving money in daily life among primary school students, and (3) Enhance financial discipline and saving behavior among students at Wat Hatsung School through the use of animation media as a learning tool. The 2D animation media on the topic of "Saving Money" was used with a sample group of 30 people, who were students from Wat Hatsung School, Mai Riang Subdistrict, Chawang District, Nakhon Si Thammarat Province. The tools used were a perception measurement scale and a questionnaire for the sample group. Satisfaction was then measured, and the results were summarized using statistical methods, namely the mean and standard deviation. The research results showed that (1) The satisfaction evaluation of the content by content experts was at a very satisfactory level, or mean (= 4.24) and standard deviation (S.D. = 0.47), and (2) The satisfaction evaluation of the media by media experts was at a very satisfactory level. or the mean (= 4.52) and the standard deviation (S. D. = 0.40) (3) The satisfaction evaluation of the 30 sample group on the content was at the highest satisfaction level, or the mean (-3.78) and the standard deviation (S. D. = 0.78) (4) The satisfaction evaluation of the 30 sample group on the media was at the very satisfied level, or the mean (= 3.80) and the standard deviation (S.D. = 0.78)